2019
DOI: 10.1002/chem.201903099
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State 13C NMR Evidence for Long Multicenter Intradimer Bonding in Zwitterion‐like Structures

Abstract: The principal values of the 13C chemical shift tensor for the β and δ polymorphs of π‐[TTF⋅⋅⋅TCNE] (TTF=tetrathiafulvalene; TCNE=tetracyanoethylene) have been analyzed to understand the abnormally long intra‐dimer bonding of singlet π‐[TTFδ+⋅⋅⋅TCNEδ−]. These structures possess 12 intradimer contacts <3.40 Å, with the shortest intra π‐[TTF⋅⋅⋅TCNE] separations involving 2‐center (2c) C−S and 3c C−C−C orbital overlap contributions between the [TTF]δ+ and [TCNE]δ−. This solid‐state NMR study compares the [TTF⋅⋅⋅TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(178 reference statements)
0
2
0
Order By: Relevance
“…Recently, solid-state 13 C NMR studies gave the first experimental support for a long, multicenter bond in the TTF-TCNE complex. [183] Chemical shift tensor analysis of the β and δ polymorphs showed significant changes compared to TTF and TCNE homodimers, indicating alterations to both πelectrons and σ-bonds upon hetero-dimer formation. This agreed with the predictions of a long bond with mixed covalent/ionic character.…”
Section: Tcne As An Acceptormentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, solid-state 13 C NMR studies gave the first experimental support for a long, multicenter bond in the TTF-TCNE complex. [183] Chemical shift tensor analysis of the β and δ polymorphs showed significant changes compared to TTF and TCNE homodimers, indicating alterations to both πelectrons and σ-bonds upon hetero-dimer formation. This agreed with the predictions of a long bond with mixed covalent/ionic character.…”
Section: Tcne As An Acceptormentioning
confidence: 97%
“…(Figure 27) Local contact potential difference measurements revealed that both conformations had similar charge, demonstrating that Kondo effect depended on the TCNE configuration. Recently, solid‐state 13 C NMR studies gave the first experimental support for a long, multicenter bond in the TTF‐TCNE complex [183] . Chemical shift tensor analysis of the β and δ polymorphs showed significant changes compared to TTF and TCNE homodimers, indicating alterations to both π‐electrons and σ‐bonds upon hetero‐dimer formation.…”
Section: Sulphur Containing Donorsmentioning
confidence: 99%